Invasive aspergillosis in solid organ transplantation: Diagnostic challenges and differences in outcome in a Spanish national cohort (Diaspersot study). Issue 11 (24th July 2021) - Gioia, Francesca; Filigheddu, Eta; Corbella, Laura; Fernández‐Ruiz, Mario; López‐Medrano, Francisco; Pérez‐Ayala, Ana; Aguado, Jose María; Fariñas, Maria Carmen; Arnaiz, Francisco; Calvo, Jorge; Cifrian, Jose Maria; Gonzalez‐Rico, Claudia; et al.
Abstract: Background: The diagnosis of invasive aspergillosis (IA) can be problematic in solid organ transplantation (SOT). The prognosis greatly varies according to the type of transplant, and the impact of prophylaxis is not well defined. Patients and Methods: The Diaspersot cohort analyses the impact of IA in SOT in Spain during the last 10 years. Proven and probable/putative IA was included. Results: We analysed 126 cases of IA. The incidences of IA were as follows: 6.5%, 2.9%, 1.8% and 0.6% for lung, heart, liver and kidney transplantation, respectively. EORTC/MSG criteria confirmed only 49.7% of episodes. Tree‐in‐bud sign or ground‐glass infiltrates were present in 56.3% of patients, while serum galactomannan (optical density index >0.5) was positive in 50.6%. A total of 41.3% received combined antifungal therapy. Overall mortality at 3 months was significantly lower ( p < 0.001) in lung transplant recipients (14.8%) than in all other transplants [globally: 48.6%; kidney 52.0%, liver 58.3%, heart 31.2%, and combined 42.9%]. Fifty‐four percent of episodes occurred despite the receipt of antifungal prophylaxis, and in 10%, IA occurred during prophylaxis (breakthrough infection), with both nebulised amphotericin (in lung transplant recipients) and candins (in the rest). Conclusions: Invasive aspergillosis diagnostic criteria, applied to SOT patients, may differ from those established for haematological patients. IA in lung transplants has a higher incidence, but is associated with a better prognosis than other transplants. Combination therapy is frequently used for IA in SOT. Prophylactic measures require optimisation of its use within this population.